Performance of Data Transmission using LoRa Module in Smart Plantation Watering Systems - Suratun Nafisah; Willy Rachman; Nurfaisal Asrafi; Ayu Sholeha; Japar Sodik; Uri Arta Ramadhani; Zunanik Mufidah; Winda Yulita (Jurnal Multidisiplin Madani, 2023)
Indonesia has a very large plantation area and is the main sector to support the community's economy. Generally, not all of the harvests obtained are good, so farmers experience losses. This condition is influenced by several factors such as plant needs that are not being met, which is why the Smart Watering System for Plantation (SWAP) is presented. SWAP is an automatic plant watering tool designed for the plantation sector by implementing a data transmission system using LoRa (Long Range) and NodeMCU ESP 8266 as a microprocessor. This research aims to determine and test data transmission performance using LoRa (Long Range). The aspects tested were testing the data transmission configuration using LoRa and delay testing in the plantation 1 and plantation 2 areas. The results shows that the plantation 2 has a better performance in terms of delay with 280,97 ms than plantation 1 that needs 322,53 ms to transmit the data